Synthesis and ionic-electronic conductivity of A-site deficient (Y, In) co-doped SrTiO3 as novel materials for mixed conductor. (October 2015) - Shan, Ke; Yi, Zhong-Zhou
Abstract: A-site-deficient (Y, In) co-doped SrTiO3 was prepared by sol–gel method. A-site deficiency improved ionic conductivity and sinterability of materials. The ionic conductivity for (Y0.08 Sr0.92 )0.93 Ti0.92 In0.08 O3−δ was 6.5 × 10 −3 S cm −1 and increased about 169% compared with (Y0.08 Sr0.92 )0.97 Ti0.92 In0.08 O3−δ at 800 °C. A-site deficiency decreased oxygen migration energy, therefore enhancing the conduction of oxygen ions. The optimized (Y0.08 Sr0.92 )0.97 Ti0.92 In0.08 O3−δ sample exhibits an electrical conductivity in the order of 0.06–0.08 S cm −1 at 100–900 °C. A possible charge compensation mechanism of A-site-deficient (Y, In) co-doped SrTiO3 is also discussed.